#BlackIsBeautiful: the radical politics of black hair. Issue 2 (26th May 2020) - Canella, Gino
Abstract : Black Lives Matter 5280 (BLM5280) posts an image on its Facebook page each morning with the caption 'Good morning #Beautiful people. #BlackIsBeautiful.' The images in this series often depict Black people in ways that challenge heteronormative conceptions of family and white beauty standards. Through feminist visual culture and digital ethnography, I show how BLM5280's photo series leverages the radical legacy of Black hair to claim symbolic and political power. I discuss my work as an allied filmmaker with the group, and examine BLM5280's online practices in relation to its local organising. Although curating images on social media may not, in itself, bring about social change, this cultural practice plays an important role in shaping perceptions of Blackness, amplifying the voices and agency of underrepresented people, and strengthening the social and emotional well-being of BLM5280's online and offline communities.